Sediment quality benchmarks for assessing oil‐related impacts to the deep‐sea benthos. (11th March 2017) - Balthis, William L; Hyland, Jeffrey L; Cooksey, Cynthia; Montagna, Paul A; Baguley, Jeffrey G; Ricker, Robert W; Lewis, Christopher
ABSTRACT: Paired sediment contaminant and benthic infaunal data from prior studies following the 2010 Deepwater Horizon (DWH) oil spill in the Gulf of Mexico were analyzed using logistic regression models (LRMs) to derive sediment quality benchmarks for assessing risks of oil‐related impacts to the deep‐sea benthos. Sediment total polycyclic aromatic hydrocarbon (PAH) and total petroleum hydrocarbon (TPH) concentrations were used as measures of oil exposure. Taxonomic richness (average number of taxa/sample) was selected as the primary benthic response variable. Data are from 37 stations (1300–1700 m water depth) in fine‐grained sediments (92%–99% silt‐clay) sampled within 200 km of the DWH wellhead (most within 40 km) in 2010 and 32 stations sampled in 2011 (29 of which were common to both years). Results suggest the likelihood of impacts to benthic macrofauna and meiofauna communities is low (<20%) at TPH concentrations of less than 606 mg kg −1 (ppm dry weight) and 700 mg kg −1 respectively, high (>80%) at concentrations greater than 2144 mg kg −1 and 2359 mg kg −1 respectively, and intermediate at concentrations in between. For total PAHs, the probability of impacts is low (<20%) at concentrations of less than 4.0 mg kg −1 (ppm) for both macrofauna and meiofauna, high (>80%) at concentrations greater than 24 mg kg −1 and 25 mg kg −1 for macrofauna and meiofauna, respectively, and intermediate at concentrations in between. Although numerical sediment quality guidelines (SQGs) are available for total PAHs and other chemical contaminants based on bioeffect data for shallower estuarine, marine, and freshwater biota, to our knowledge, none have been developed for measures of total oil (e.g., TPH) or specifically for deep‐sea benthic applications. The benchmarks presented herein provide valuable screening tools for evaluating the biological significance of observed oil concentrations in similar deep‐sea sediments following future spills and as potential restoration targets to aid in managing recovery. Integr Environ Assess Manag 2017;13:840–851. Published 2017. This article is a US Government work and is in the public domain in the USA. Key Points: Paired sediment contaminant and benthic infaunal data from prior studies following the 2010 Deepwater Horizon oil spill in the Gulf of Mexico were analyzed using logistic regression modeling to derive sediment quality benchmarks for assessing risks of oil‐related impacts to the deep‐sea benthos. This work provides an empirical framework for evaluating risks of impaired benthic condition (reduced taxa richness) in Gulf of Mexico deep‐sea sediments in relation to increasing concentrations of 2 oil‐related indicators (total petroleum hydrocarbons and total polycyclic aromatic hydrocarbons). The benchmarks developed in this study will provide valuable screening tools for evaluating the biological significance of observed oil concentrations in similar deep‐sea sediments following future spills and as potential restoration targets to aid in managing recovery.